ASK1 modulates the expression of microRNA Let7A in microglia under high glucose in vitro condition - Song, Juhyun; Lee, Jong Eun (Frontiers in Cellular Neuroscience, 2015)
Hyperglycemia results in oxidative stress and leads to neuronal apoptosis in the brain. Diabetes studies show that microglia participate in the progression of neuropathogenesis through their involvement in inflammation in vivo and in vitro. In high-glucose-induced inflammation, apoptosis signal regulating kinase 1 (ASK1) triggers the release of apoptosis cytokines and apoptotic gene expression. MicroRNA-Let7A (miR-Let7A) is reported to be a regulator of inflammation. In the present study, we investigated whether miR-Let7A regulates the function of microglia by controlling ASK1 in response to high-glucose-induced oxidative stress. We performed reverse transcription polymerase chain reaction, Taqman assay, real-time polymerase chain reaction, and immunocytochemistry to confirm the alteration of microglia function. Our results show that miR-Let7A is associated with the activation of ASK1 and the expression of anti-inflammatory cytokine (interleukin (IL)-10) and Mycs (c-Myc and N-Myc). Thus, the relationship between Let-7A and ASK1 could be a novel target for enhancing the beneficial function of microglia in central nervous system disorders.